PERGESERAN NILAI PENDIDIKAN AKHLAK DALAM PROSESI KHITBAH NIKAH DI DUSUN MELINJEE (Lembaga Studi Agama dan Masyarakat Aceh (LSAMA), 2024)
The marriage sermon is a process by which a man or his family conveys their desire to marry a woman to the woman's family. In this sermon procession there are morals or ethics between the bride and groom and their families which must be maintained and maintained in order to create a harmonious relationship between the two families. This research aims to find out how the value of moral education shifts in the marriage sermon procession in Melinjee village. The research used interview methods with figures in the Melinjee hamlet, parents who had married off their children, and the perpetrators of the sermon itself. Apart from that, the author also uses observation methods regarding the implementation, planning and shifts that occur in the marriage sermon procession. The results of the research that the author found were a shift in the value of moral education in the marriage sermon procession in: visiting the prospective bride and groom after the application/engagement event without being accompanied by the muhrim 48%, holding meetings outside without being accompanied by the muhrim 61%, picking up/picking up the prospective husband/wife at the house upstairs as far as parents know 61%, taking/inviting to go out without the muhrim 61%, going to proposal events, wedding parties, between the groom (linto baro) 19%, riding on motorbikes 60%, determining the dowry by the prospective bride 100%, take pride in 62% of the proposal gifts, and 50% of the pre-wedding photos.